(untitled) (Journal of the College of Basic Education, 2024)
After the end of the rule of the Chehab emirate in the Emirate of Mount Lebanon in 1842, the Ottoman Empire appointed the Austrian governor Omar Pasha in the same year, who ruled Mount Lebanon for a short period due to his bias towards the Masonic sect, which prompted the Druze sect to declare a revolution against him that ultimately led to his removal.